Sesquiterpenoid Hormones Farnesoic Acid and Methyl Farnesoate Regulate Different Gene Sets in Shrimp Neocaridina davidi Hepatopancreas - Yehui Luan; Wenyan Nong; Wai Lok So; Jerome Ho Lam Hui (Biomolecules)
Sesquiterpenoid hormones such as the juvenile hormone and methyl farnesoate (MF) are well known to respectively control the development and reproduction in insects and crustaceans (such as shrimp, crabs, and lobsters). In recent years, the sesquiterpenoid hormone farnesoic acid (FA) has also been identified in other non-insect/crustacean invertebrates; despite this, their regulatory roles remain poorly understood. Here, we carried out the in vitro treatments of MF and FA on the hepatopancreas of female adult shrimps Neocaridina davidi. Transcriptomic analyses revealed a total of 65 and 112 differentially expressed genes in the MF- and FA-treated hepatopancreas at 3 h post-treatment, respectively. Gene pathway enrichment analyses further suggested that the two sesquiterpenoid hormones regulate different sets of genes, with the gene pathway involved in pancreatic secretion enriched only in the FA-treated hepatopancreas. This study demonstrates the differential regulatory roles between sesquiterpenoid forms, which warrants further investigation into the functions of FA in crustaceans.